Fibrous Tumor of the Breast: Case Report of an Underrecognized Entity. (26th December 2010) - Chowdhury, Nilotpal; Bhat, Ramachandra V.; Barman, Partho Protim
Abstract : Fibrous tumor of the breast is an underappreciated, distinctive, benign, nonrecurrent lesion of the breast. The cytological features of this condition are not well characterized. We present a case report of a 30-year-old female presenting with a hard mass in her right breast. Fine needle aspiration showed smears of low cellularity showing a few clusters and sheets of mostly uniform benign epithelial cells, some of which were lined by myoepithelial cells. Scattered bipolar bare nuclei or stromal fragments were not seen. Excision with subsequent histopathological examination revealed a well-circumscribed, heavily collagenous tumor with atrophy and replacement of the epithelial and ductal elements of the breast, and diagnosed as fibrous tumor. Being nonrecurrent, it is important to distinguish this lesion from fibromatosis of the breast.